Using Small Group Discussion for English Speaking at Vocational High School (SMKN) 1 Pujut - Nuraini, Ella; Amrullah; Melani, Boniesta Zulandha; Amin, Muhammad (Program Studi Pendidikan Bahasa Inggris, 2025)
This study investigates the significance of the Small Group Discussion (SGD) method in enhancing students’ English-speaking performance at SMKN 1 Pujut. The research applied a quasi-experimental design involving two groups: an experimental group taught using Small Group Discussion and a control group taught through conventional methods. Both groups consisted of 34 students. The data were collected through pre-test and post-test to measure students’ speaking ability, focusing on four aspects: grammar, vocabulary, pronunciation, and fluency. The treatment was conducted in three meetings. During the learning process, students in the experimental group actively participated in group discussions, while those in the control group followed traditional teacher-centered instruction. The results were analyzed using an independent samples t-test. The findings showed that there was a significant difference between the two groups, where the experimental group achieved a higher mean score of 66.76 compared to 53.67 in the control group, with a t-value of -6.717 and a significance level (p) < 0.05. The results indicate that the Small Group Discussion method helps improve students’ speaking achievement and encourages more active and confident participation during classroom interaction.